Grid Impact Study of Micro-Grid with an Improved Transient Response using PV Panel in MATLAB-SIMULINK - Shah, Shiv Kumar; Adhikari Thapa, Sanjog (Journal of Advanced College of Engineering and Management, 2023)
The paper present a system that convert a power generated from a renewable resources to a source having same voltage and frequency with respect to traditional power plant. As the conventional fossil fuel resources such as Coal, Diesel, Gas etc is limited in quantity which will run out very soon. Hence all the researchers throughout the world are looking for alternative form of energy[1]. As a consequence the penetration of WIND & PV – generated electrical energy into the grid system is increasing exponentially worldwide [2]. The paper consist of PV array, boost converter, 3phase VSC Inverter, synchronous generator and utility grid. PV system has low conversion efficiency, so to improve conversion efficiency it is important for PV system to work always at its maximum power point. Maximum Power Point Tracker (MPPT) control technique is used to get maximum power as possible [3]. The voltage source inverter interface with grid and transfer an energy drawn from PV array to the grid by keeping the common voltage & frequency constant. The simulation results such as voltage, current, output power for each various combination have been recorded. The simulation has been accomplished in a Software of MATLAB Math Works.